Language, society and power : an introduction - Mooney, Annabelle, 1974-; Evans, Betsy, 1966- (Routledge, Taylor & Francis Group, 2015)
"Language, Society and Power is an introductory text to studying language in a variety of social contexts. It examines the ways in which language functions, how it influences thought and how it varies according to age, ethnicity, class and gender. This fourth edition has been completely revised to include recent developments in theory and research, and offers new chapters on Linguistic Landscapes and Global Englishes, updated and expanded further reading and student project sections, and a brand new companion website"-- Resumé vydavatele